GE_GERICHTE C/30414/2017 vom 5. November 2018 - GE Cour de justice (2018)
PROCÉDURE SOMMAIRE ; MAINLEVÉE PROVISOIRE; TITRE DE MAINLEVÉE ; RECONNAISSANCE DE DETTE ; PREUVE FACILITÉE | LP.82.al1; CPC.327.al3.letb; CO.104.al1